Islamic finance of the Gulf monarchies - A.O. Filonik; V.A. Isaev (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper analyzes financial business potential in the Gulf monarchies. They have practically realized the idea of the Islamic banking industry that currently operates well enough in spite of a rather short period of its modern history. The purpose of the paper is to specify the correlation between general and particular aspects of the process using comparative analysis and critical re-evaluation of facts. The study proceeds from that the Gulf states have their special model of banking activity spread far beyond their limits reaching across Muslim-populated areas and penetrating into some niches of the economically advanced world. However, the whole industry is not free of weak points due to diseases of growth. Some bankers tend to simplify their operations and, thus, shy away the rigid Sharia standards. The current troubles are caused mainly by the reasons of technical and institutional origin. Nevertheless, some difficulties are of another ground and used to be met in the yet unfooted plains. The paper analyzes the fact that the Islamic capital has begun just recently to better cope with the relatively new models of trade, such as project and commercial financing, factoring, Islamic funding, micro-financing etc. The bankers have realized that these issues are of great importance for the industry's future. Islamic banks have to compete with the conventional banks having rather deep roots in the economy of the Gulf states and other Muslim-majority countries. The situation affects the Islamic business and makes it spend much effort on maintaining the level comparable with that of banks from the West. They still have to work very hard in this field against the fact that many problems that are now unfriendly to Islamic banks were overcome by their Western counterparts long ago. The conclusion has been made that numerous difficulties and dead ends faced by the Islamic institutions prevent them from a quick move to greater success in spite of their wealth and governmental support. The core problems of today's Sharia banks are the insufficient level of standardization, certification, lack of qualified staff and improvements as well in their Sharia boards followed by the easy focusing on the unbanked entities within the Islamic sector's scope.